Influence of Commercial Inert Glass Addition on the Mechanical Properties of Commercial Synthetic Hydroxyapatite - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2013)
In this study, microstructures and mechanical properties of commercial synthetic hydroxyapatite (CSHA)-commercial inert glass (GIG) composites were investigated. The goal of development of CSHA-CIG composite is to improve mechanical properties of hydroxyapatite. For this reason, CSHA powders were mixed with 5 and 10 wt% GIG separately. Pressed samples were sintered at the different temperatures in the range of 1000-1300 degrees C. The physical and mechanical properties were determined by measuring density, compression strength, the Vickers microhardness. Structural characterization was carried out with X-ray diffraction and scanning electron microscopy studies. The experimental results were discussed to determine optimum amount of reinforcement material and the effect of sintering temperature on the microstructure and the mechanical properties of CSHA GIG composites. The mechanical properties of composites decreased with increasing GIG content. The highest mechanical properties and the highest density were obtained in CSHA-5 wt%CIG composite sintered at 1300 degrees C. DOI: 10.12693/APhysPolA.123.427
Keywords: COMPOSITES; BHA